2012
DOI: 10.1038/bmt.2012.144
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF mobilized vs conventional donor lymphocytes for therapy of relapse or incomplete engraftment after allogeneic hematopoietic transplantation

Abstract: There is little data comparing the activity and toxicity of donor lymphocyte therapy with granulocyte (G)-CSF-mobilized cells (G-donor lymphocyte infusion (DLI)) with the conventionally collected DLI (C-DLI) after allogeneic blood or marrow transplantation. We retrospectively evaluated 67 patients to compare the efficacy and toxicity of GCSF-mobilized DLI with C-DLI in the treatment of relapse of malignant disease or poor donor engraftment post transplant. We assessed clinical outcomes that may represent the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…A potent GVL effect was expected in DLI strategy, but it is ideal to control GVHD at a mild level. Many researchers tried to enhance the GVL of infused donor T cells, while decreasing DLI‐related toxicities using new strategies such as granulocyte–colony‐stimulating factor (G‐CSF)‐mobilized peripheral blood progenitor cell infusion or allodepleted donor T cells . We used traditional DLI without G‐CSF stimulation or special depletion in this study, and we also showed a low incidence of severe and lethal aGVHD; most of the mortality was from disease relapse or refractory disease rather than GVHD.…”
Section: Discussionmentioning
confidence: 89%
“…A potent GVL effect was expected in DLI strategy, but it is ideal to control GVHD at a mild level. Many researchers tried to enhance the GVL of infused donor T cells, while decreasing DLI‐related toxicities using new strategies such as granulocyte–colony‐stimulating factor (G‐CSF)‐mobilized peripheral blood progenitor cell infusion or allodepleted donor T cells . We used traditional DLI without G‐CSF stimulation or special depletion in this study, and we also showed a low incidence of severe and lethal aGVHD; most of the mortality was from disease relapse or refractory disease rather than GVHD.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, G-CSF-primed DLI could be a potential approach to treat relapsed leukemia post HSCT; however, in a recent clinical study, G-CSF-primed DLI was not shown to be superior to conventional DLI. 43 Consistent with this study, Curley et al 44 performed a retrospective analysis of 32 relapsed acute leukemia patients after allo-HSCT. Nineteen of them received Flu, Cytarabine and G-CSF (FLAG) induction chemotherapy followed by G-CSF-mobilized DLI and the rest of 13 patients received the same stepwise therapy but no DLI.…”
mentioning
confidence: 76%
“…[12][13][14] Administration of DLI has been shown to promote full-donor chimerism 15 and this may result in lower relapse rates. 14,[29][30][31][32] We postulated that early mixed T-cell chimerism may be effectively converted to full-donor T-cell chimerism by using preemptive low-dose DLI, even in the absence of relapse or persistence of malignancy. We also postulated that continuation, rather than withdrawal of post transplant immunosuppressive therapy, following DLI may minimize the risk of acute GVHD.…”
Section: Discussionmentioning
confidence: 99%